2010
DOI: 10.1176/appi.ps.61.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Depression Treatment Utilization Among Latinos: Utility of Four Stigma Measures

Abstract: Objectives Stigma associated with mental illness is an important yet understudied issue among Latinos. This study examined the psychometric properties of four stigma measures with a sample of Spanish-speaking Latino primary care patients. The study evaluated the scale for Perceived Discrimination Devaluation (PDD), Stigma Concerns About Mental Health Care (SCMHC), the Latino Scale for Antidepressant Stigma (LSAS), and the Social Distance (SD) scale. Methods Participants (N=200) were low-income Latinos who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 20 publications
6
40
1
Order By: Relevance
“…The psychometric properties of both scales were assessed with a sample of 200 low-income Latinos screened for depression. Latinos who scored high on both the SCMHC (OR .64, p \ .05) and the LSAS (OR .77, p \ .05) were less likely to take antidepressant medication (Interian et al 2010). The current study used Cronbach's alpha to measure each scale's internal consistency and found good internal reliability for both the SCMHC (.83) and the LSAS (.79).…”
Section: Stigma Towards Depression Treatment Was Assessed With the Spmentioning
confidence: 67%
See 1 more Smart Citation
“…The psychometric properties of both scales were assessed with a sample of 200 low-income Latinos screened for depression. Latinos who scored high on both the SCMHC (OR .64, p \ .05) and the LSAS (OR .77, p \ .05) were less likely to take antidepressant medication (Interian et al 2010). The current study used Cronbach's alpha to measure each scale's internal consistency and found good internal reliability for both the SCMHC (.83) and the LSAS (.79).…”
Section: Stigma Towards Depression Treatment Was Assessed With the Spmentioning
confidence: 67%
“…Health Care (SCMHC) scale, and the Latino Scale for Antidepressant Stigma (LSAS) (Interian et al 2010). The SCMHC is a 3-item scale measuring stigma-related barriers to depression treatment (i.e., avoid seeking treatment due to embarrassment about discussing personal matters with others, fear of what others might think, or thoughts that family members would not approve of the treatment).…”
Section: Stigma Towards Depression Treatment Was Assessed With the Spmentioning
confidence: 99%
“…Models 1 and 2 sought to answer the question, do the data support perceived devaluation–discrimination as a single factor (model 1), or as 2 factors (model 2)? Model 3 attempted to determine the plausibility of positive and negative dimensions of perceived stigma as proposed by others (Interian et al., ). Finally, motivated by evidence from prior factor analytic studies that extracted separate “method factors” to adjust for positively and negatively worded items (Marsh et al., ), we specified models 4 (a single PDD factor) and 5 (two PDD factors) as analogs of models 1 and 2, while statistically adjusting for method effects.…”
Section: Methodsmentioning
confidence: 99%
“…However, the distinction between the 2 dimensions in the PDD has been obscured in some research, where a single score has been created from all items (Keyes et al., ), or 2 dimensions are assumed via creation of 2 subscales (Smith et al., ) but not psychometrically evaluated. Further, evidence from exploratory factor analysis has been presented that suggest that the positively and negatively worded items may induce separate latent factors that reflect “perceived acceptance and nonnegative evaluation” and “perceived discrimination and negative evaluation,” respectively (Interian et al., ). To our knowledge, there are no confirmatory factor analytic (CFA) studies that have described the factor structure of the PDD.…”
mentioning
confidence: 99%
“…Thus stigma is a prominent concern among racialethnic minority groups and a major contributor to lesser treatment involvement and lower adherence." 32 Since it is estimated that approximately twothirds of children in the juvenile court system have some form of mental health problem, 33 a substantial number of those children may fear disclosure of their mental health conditions or treatments. 34 Other groups of LGBTQ children may fear disclosure of their sexual orientation because of strict religious or cultural taboos.…”
Section: Juvenile Courtsmentioning
confidence: 99%